Peran Kepemimpinan Dalam Menekan Terjadinya Kecurangan Penerimaan Kas Pada Industri Hotel - I Putu Arnawa; A.A.Istri M.Septiviari; I Wayan Tuwi (Public Service and Governance Journal, 2023)
This study is entitled "The Role of Leadership in Suppressing the Occurrence of Fraud in Cash Receipts." This study aims to analyze and identify the role and leadership attitude of the Chief Accountant to suppress, minimize, and avoid fraud committed in the process of cash receipts in a hotel that has its own management (not professional management). Based on the data sources that have been identified, it turns out that there is still the potential for fraud to occur in cash receipts. Various data sources that have been obtained say that the occurrence of fraud is caused by the workers themselves. Factors causing the occurrence of fraud come from several things, one of which comes from the mindset and behavior of the perpetrators of the fraud itself. Other factors from the corporate environment can also lead to acts of fraud, namely the inconvenience that is obtained by the perpetrator in working at the company. We then analyze the data sources that have been collected to obtain clear information regarding the occurrence of the fraud. The conclusion that can be drawn from the results of data analysis and identification, that the occurrence of fraudulent cash receipts occurs due to the lack of a leader's attitude in the control and supervision strategy carried out. The attitude of a Chief Accountant who pays little attention to these problems makes it easy for fraud to occur. The effectiveness applied by a Chief Accountant and the adoption of a leadership style are still relatively low. It is hoped that the application of the leadership attitude of a Chief Accountant will provide solutions that have a significant effect and be able to overcome this so that it does not happen again in a company.